1984
DOI: 10.1093/clinchem/30.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin-like immunoreactivity in normal human plasma and urine, as detected by a solid-phase radioimmunoassay.

Abstract: Reports on the presence of digoxin-like immunoreactive substance(s) (DLIS) in the plasma and urine of several animal species and a few human test subjects prompted us to undertake to confirm the presence of DLIS in plasma and urine of normal persons and to investigate some characteristics of this antibody-DLIS binding. For this purpose we used a modified radioimmunoassay kit involving antidigoxin antibody-coated test tubes and 125I-labeled digoxin to measure DLIS in urine and concentrated plasma of ostensibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…DLIF is an endogenous material that is released into the circulation under different physiologic and pathologic conditions (2,3,(9)(10)(11)(12)(13)(14)(15)(16). It has been found in almost all the newborns tested for this substance (4)(5)(6)(7)(8), but in only 30% of older children (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DLIF is an endogenous material that is released into the circulation under different physiologic and pathologic conditions (2,3,(9)(10)(11)(12)(13)(14)(15)(16). It has been found in almost all the newborns tested for this substance (4)(5)(6)(7)(8), but in only 30% of older children (19).…”
Section: Discussionmentioning
confidence: 99%
“…An endogenous substance cross-reacting with anti-digoxin antibodies was first reported in animals by Gruber et al (1). Subsequently, it was found in a variety of physiologic and pathologic conditions including pregnancy, premature and full-term infants, hepatic, renal, and cardiac diseases, essential hypertension (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Several observations have suggested that this material may be an endogenous digoxin-like factor, which, like cardiac glycosides, inhibits Na þ K þ -ATPase (14).…”
mentioning
confidence: 97%
“…Before the analysis, each plasma (serum) or urine sample was extracted on fresh SepPak C18 cartridges (Waters Associates) as previously described (15). A 2-mL sample was applied to each cartridge that had been previously activated with 4 mL of methanol followed by 20 mL of distilled water.…”
Section: Preparation Of Placental Membranesmentioning
confidence: 99%
“…The extracts were evaporated under reduced pressure, the dry residues were redissolved in 250 zL of incubation buffer, and 100 .L of this solution were then used in the radioreceptor assay. Extraction of urine or plasma (serum) samples with SepPak C18 cartridges avoided interferences from ions (such as K) (15), proteins, or fatty acids. More than 99.5% of the albumin or total proteins in the sera, and more than 99% of the free fatty acids were eliminated by the washings of the resin.…”
Section: Preparation Of Placental Membranesmentioning
confidence: 99%
“…Because DLIS concentrations in plasma or serum samples from normal adult subjects are frequently near the limit ofsensitivity for RIA methods (6)(7)(8), the sample usually must be concentrated before analysis, to increase the precision of the assay. In contrast, urine of adults and newborns have DLIS concentrations four-to sixfold those in plasma, and the direct RIA could be preferable (8).…”
Section: Urinary Excretion Of Digoxln-ilke Immunoreactlvity After Phymentioning
confidence: 99%